2017
DOI: 10.7717/peerj.4115
|View full text |Cite
|
Sign up to set email alerts
|

Examining publication bias—a simulation-based evaluation of statistical tests on publication bias

Abstract: BackgroundPublication bias is a form of scientific misconduct. It threatens the validity of research results and the credibility of science. Although several tests on publication bias exist, no in-depth evaluations are available that examine which test performs best for different research settings.MethodsFour tests on publication bias, Egger’s test (FAT), p-uniform, the test of excess significance (TES), as well as the caliper test, were evaluated in a Monte Carlo simulation. Two different types of publication… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In addition, the publication bias in the meta-analysis likely led to small-study effects, where the smaller studies might have shown larger treatment effects. The Egger test is a statistical test for small-study effects that may detect increased bias with increasing numbers of trials on the basis of a linear regression model [ 24 , 25 ]. In this study, publication bias was assessed using the Egger test.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the publication bias in the meta-analysis likely led to small-study effects, where the smaller studies might have shown larger treatment effects. The Egger test is a statistical test for small-study effects that may detect increased bias with increasing numbers of trials on the basis of a linear regression model [ 24 , 25 ]. In this study, publication bias was assessed using the Egger test.…”
Section: Methodsmentioning
confidence: 99%
“…The PB against non-significant studies is another threat that biases the combined estimates of the population ES. It is a real and important threat to the validity of conclusions based on meta-analyses that has been well studied and documented for decades (Mueller, 2018;Rothstein et al, 2005;Schneck, 2018;van Aert et al, 2019). Graphically, PB produces a step in the expected distribution of p-values that can be very similar to that produced by pH.…”
Section: Assessing the Prevalence Of Phmentioning
confidence: 99%
“…Publication bias was assessed subjectively by visual evaluation of funnel plots. Furthermore, Egger’s test and Begg’s test were both conducted using Stata 13.0 (Stata Corp, College Station, Texas, USA), and P value less than 0.05 indicated possibility of publication bias [9], in which case, the Duval and Tweedie’s trim and fill method with random effect would be performed to estimate the adjusted effect size [10].…”
Section: Methodsmentioning
confidence: 99%